Left-handedness and time pressure in elite interactive ball games - Loffing, F. (Biology letters, 2017)
According to the fighting hypothesis, frequency-dependent selection gives relatively rarer left-handers a competitive edge in duel-like contests and is suggested as one mechanism that ensured the stable maintenance of handedness polymorphism in humans. Overrepresentation of left-handers exclusively in interactive sports seems to support the hypothesis. Here, by referring to data on interactive ball sports, I propose that a left-hander's advantage is linked to the sports` underlying time pressure. The prevalence of left-handers listed in elite rankings increased from low (8.7%) to high (30.39%) time pressure sports and a distinct left-hander overrepresentation was only found in the latter (i.e. baseball, cricket and table tennis). This indicates that relative rarity and the interactive nature of a contest are not sufficient per se to evoke a left-hander advantage. Refining the fighting hypothesis is suggested to facilitate prediction and experimental verification of when and why negative frequency-dependent selection may benefit left-handedness.